Re-arrange the equation to make g the subject. Show all working out. f + 4(g − h) = x

Question

Re-arrange the equation to make g the subject. Show all working out. f + 4(g − h) = x

in progress 0
Valentina 1 month 2021-09-16T15:57:57+00:00 1 Answer 0 views 0

Answers ( )

    0
    2021-09-16T15:59:48+00:00

    Answer:

    g=x-f+4h/4

    Step-by-step explanation:

    f+4(g-h)=x

    f+4g-4h=x

    4g-4h=x-f

    4g=x-f+4h

    g=x-f+4h/4

    please mark as brainliests

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )